Fruit Size Characteristics and Growth Rate of Cucumber ’Puang’ - Suntaree Yingjajaval; Thiva Buppaprasert (Agriculture and Natural Resources, 1993)
Harvested fresh-market cucumbers ’Puang’ were sampled for the measurement of their diameter, length, fresh mass and volume. Sampling was from the same experiment, which was set to study the effect of irrigation and fertilizer rates on the yield. With a split-plot design, the main plots were 3 levels of irrigation rate: 10095, 150% and 200% of potential evapotranspiration (PET), based on Penman method of 15 years average data of Kamphaeng Saen. Water was applied in furrow twice a week. The sub-plots comprised 4 levels of 2:1:1 ratio of fertilizer. These were 10 kgN, 5 kg available P2O5 and 5 kg K2O per rai in the first level of application, while fertilizer levels 2, 3, 4, were 2, 3, and 4, times the first rate. Fertilizer was split equally into 6 applications. The growing period of cucumber was 62 days. Harvest began 39 days after seeding. Experimental treatments showed no effect on the size characteristics of the fruit. The fresh mass (M in g) equals 1.034V, where V is volume in cm3, with the specific gravity = 1.041 Mg m-3. Cucumber comprised water up to 95.4% of its fresh mass. Fruit length was 2.26 times of the diameter at the middle of the fruit. Of the 361 cucumbers measured, the average fresh mass was 40.81±15.87 g, the length was 6.98±1.05 cm and the diameter was 3.11±0.42 cm. The relationship between the mass and the diameter and length was M = 0.504D1.795L1.191 However, two other relationships, namely, M = 19.572+2.749(DL) and M = 0.4208(DL)1.472 gave equally good fit. In describing growth rate, the diameter and length of fruit were measured regularly in the morning (9-11 h) and afternoon (14-16 h) from the days of fruit setting (DAFS). Using the above relationships, the fruit mass was calculated from the size parameters. The growth rates of diameter, length as well as mass were found to he an exponential function of DAFS, in a general form of Y = A exp(BxDAFS). The results showed that the diameter would expand at the rate of 1.41, the length at 1.36 and the mass at 2.75 times per day. Therefore, cucumber would expand at so fast a rate that 90% of all the cucumbers were ready for harvest within 5 days after fruit setting, and require daily harvesting. Cucumbers from the plots receiving water rate of 200% of PET could be harvested 3/4 day earlier than those from the 100% of PET plots, while fertilizer rates resulted in only 1/4 day difference. Of all the fertilizer rates, level 1 gave the best growth. Interestingly, it was found that the growth rate during daytime (a period of 5 hours from 9-14 h) was proportionally high in comparison with the rate during the rest of the day until the following morning. The size parameters had the growth rate ratio of 1:1.2 and the mass 1:1.6 during the two time periods. Apparently, the availability of photosynthate from the leaves to the fruit was necessary for lowering of the osmotic potential, so that water could flow into the fruit for its expansion. Cucumbers in the plots that received irrigation rates at 150% and 200% of PET had higher mass accumulation rate during daytime than those in the 100% of PET plots.